A influência de Jacob Burckhardt e o conceito de força plástica no pensamento de Nietzsche - Lima, Márcio José Silva (2018)
The purpose of the present work is to analyze the influence of the Swiss historian Jacob Burckhardt and, from this analysis, to understand the concept of plastic power in Nietzsche’s philosophy. We raise the hypothesis that the themes presented in Burckhardt’s thought such as, the ideal of greatness, history as a utility for life, the influence of art in the process of creation, the critical of historicism and the progress of history, they eventually contributed to the construction of Nietzsche’s historical thought present in his Second Untimely Meditation: and, above all, the concept of plastic power. However, we do not mean that Nietzsche’s philosophy is a faded copy of Burckhardt’s ideas. We intend to demonstrate that the reading that the philosopher made of the historian allowed, through a productive appropriation, the development of his own thinking. To our hypothesis we support ourselves in texts of the aforementioned thinkers and in the studies of the commentators on the subject. Considering that the concept of plastic power is a theme that is not much studied by philosophy, it was also necessary a proper exercise of interpretation. Thus, it was possible to demonstrate how such a concept was present, although treated differently, in the mature phase of Nietzsche’s thought. We will support the idea that the plastic power pervades Nietzsche’s philosophy, from his youth to the period in which the philosopher treats Life as a Desire for Power and Eternal Recurrence.